The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.7554/elife.44821
|View full text |Cite
|
Sign up to set email alerts
|

Natural Tr1-like cells do not confer long-term tolerogenic memory

Abstract: IL-10-producing Tr1 cells promote tolerance but their contributions to tolerogenic memory are unclear. Using 10BiT mice that carry a Foxp3-eGFP reporter and stably express CD90.1 following IL-10 production, we characterized the spatiotemporal dynamics of Tr1 cells in a house dust mite model of allergic airway inflammation. CD90.1+Foxp3-IL-10+ Tr1 cells arise from memory cells and rejoin the tissue-resident memory T-cell pool after cessation of IL-10 production. Persistent antigenic stimulation is necessary to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Since Tr1 cells are induced in the periphery (29) and are therefore antigen-experienced, they are thought to be memory CD4 + T cells and behave as such. Evidence to the contrary was introduced in an airway allergy model in which Tr1-like cells substantially reduced airway inflammation in an acute inflammatory setting but showed no role during re-challenge despite being present as resident memory cells (42).…”
Section: Classification Of Tr1 Cells and Mechanisms Of Their Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Tr1 cells are induced in the periphery (29) and are therefore antigen-experienced, they are thought to be memory CD4 + T cells and behave as such. Evidence to the contrary was introduced in an airway allergy model in which Tr1-like cells substantially reduced airway inflammation in an acute inflammatory setting but showed no role during re-challenge despite being present as resident memory cells (42).…”
Section: Classification Of Tr1 Cells and Mechanisms Of Their Inductionmentioning
confidence: 99%
“…Since Tr1 cells are induced in the periphery ( 29 ) and are therefore antigen-experienced, they are thought to be memory CD4 + T cells and behave as such. Evidence to the contrary was introduced in an airway allergy model in which Tr1-like cells substantially reduced airway inflammation in an acute inflammatory setting but showed no role during re-challenge despite being present as resident memory cells ( 42 ). The conclusion that Tr1-like cells did not contribute to tolerogenic memory was primarily based on the finding that inflammation was not enhanced in the recall response upon the in vivo depletion of IL-10-producing T cells.…”
Section: Classification Of Tr1 Cells and Mechanisms Of Their Inductionmentioning
confidence: 99%
“…Rather, Th17 cells are first converted to exTh17 cells during the inflammatory process. Among the surface markers of exTh17, in addition to CD161, CCR6, which maintains Th17, CXCR3 is also expressed [ Jung, S et al, 2023 ; Yadava, K et al, 2019 ]. Although these exTh17 cells no longer secrete IL-17, they still retain some inflammatory properties, such as the production of cytokines including IL-2, TNF, IFN-γ, and GM-CSF [Yadava, K et al, 2019].…”
Section: Cd4 + Trm May Originate From Th17 and Tregmentioning
confidence: 99%
“…9a-c). This suggested that CAR expression and function in Teff cells is increased in response to inflammation, analogous to Tr1 cell dynamics in vivo 28 . Using an orthologous approach to induce intestinal inflammation in wild type or CAR-deficient mice—soluble anti-CD3 injection 23 — we confirmed that CAR was required for anti-CD3 ( i.e ., inflammation)-induced IL-10 upregulation by endogenous effector and regulatory T cell subsets in the siLP, but not the spleen, and was dispensable for steady-state IL-10 expression in T cells from unmanipulated mice (Extended data Figure 9d-f).…”
mentioning
confidence: 92%